Economic survey of Latin America - United Nations. Economic Commission for Latin America; Economic Commission for Latin America (Santiago De Chile : United Nations, 1983)
This work is made up of three parts : trends in the Latin American economy in 1981; the economic evolution of the individual countries; and effective real exchange rate.
obn 21/01/2019
Ref.
Keywords: Economic conditions-1945-; Economic history; Latin America